Semiconductor detector systems - Spieler, Helmuth (Oxford University Press, 2005)
Discussing the many facets of highly integrated semiconductor detector systems, this comprehensive text provides an application-oriented introduction to sensors and electronics.
Keywords: Semiconductor nuclear counters.; elektronické knihy; electronic books